2023
DOI: 10.3389/fmicb.2023.1222503
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the therapeutic potentials of Lactobacillus johnsonii vs. Lactobacillus acidophilus against vulvovaginal candidiasis in female rats: an in vivo study

Abstract: BackgroundVulvovaginal candidiasis (VVC) is a highly prevalent illness affecting women globally. Lactobacilli, which make up the majority of healthy vaginal microbiota (VMB), serve as a powerful barrier against infections. Probiotic therapy has been recommended for the treatment or prevention of VVC.Aim of workTo compare the in vivo therapeutic effects of Lactobacillus johnsonii (B-2178) vs. Lactobacillus acidophilus (LA-5®) on VVC in a rat model, particularly highlighting the immune response of the host vagin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…56,57 Previous studies have reported that L. reuteri and L. johnsonii play a very important role in promoting immune tolerance, especially L. reuteri, in intestinal immune tolerance. [58][59][60] Therefore, we believe that the lack of L. reuteri and L. johnsonii in the gut of the offspring fed by the Fut8 +/− maternal mice is the key reason for their poor immune tolerance. In order to confirm this conjecture, we further supplemented the offspring fed by Fut8 +/− mothers with L. reuteri and L. johnsonii (Fig.…”
Section: Papermentioning
confidence: 99%
“…56,57 Previous studies have reported that L. reuteri and L. johnsonii play a very important role in promoting immune tolerance, especially L. reuteri, in intestinal immune tolerance. [58][59][60] Therefore, we believe that the lack of L. reuteri and L. johnsonii in the gut of the offspring fed by the Fut8 +/− maternal mice is the key reason for their poor immune tolerance. In order to confirm this conjecture, we further supplemented the offspring fed by Fut8 +/− mothers with L. reuteri and L. johnsonii (Fig.…”
Section: Papermentioning
confidence: 99%
“…The therapeutic effects of L. johnsonii B-2178 and Lactobacillus acidophilus were tested in a rat model of vulvovaginal candidiasis and observed that both lactobacilli reduced C. albicans vaginal load and hyphae formation and significantly reduced proinflammatory cytokines IL-17 and IFNg. Interestingly, only L. johnsonii B-2178 protected the vaginal mucosa epithelium from histopathological changes (Elfeky et al, 2023), suggesting that the presence of L. johnsonii in the reproductive tract may help to control the growth of pathogens and maintain a healthy environment (Figure 1).…”
Section: Johnsonii and The Reproductive Systemmentioning
confidence: 99%
“…L. johnsonii 6084 alleviated sepsis-induced organ injury by modulating gut microbiota. Vazquez-Munoz et al discovered L. johnsonii had excellent probiotic properties and can prevent or treat mucocutaneous candidiasis [86], especially vulvovaginal candidiasis [87], and that L. johnsonii UBLJ01 is a potential candidate for vaginal probiotics [88]. L. johnsonii has also be found to delay osteoarthritis progression [89] and alleviate the development of acute myocardial infarction [90].…”
Section: Liver Diseasesmentioning
confidence: 99%